2021
DOI: 10.1523/eneuro.0338-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Self-Delivering Anti-CCL3 FANA Oligonucleotide as an Innovative Approach to Target Inflammation after Spinal Cord Injury

Abstract: Secondary damage after spinal cord injury (SCI) occurs due to a sequence of events after the initial injury, including exacerbated inflammation that contributes to increased lesion size and poor locomotor recovery. Thus, mitigating secondary damage is critical to preserve neural tissue and improve neurological outcome. In this work we examined the therapeutic potential of a novel antisense oligonucleotide with special chemical modifications (FANA ASO) for specifically inhibiting an inflammatory molecule in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…FANA ASOs, in particular, have been receiving increased attention. In the past year, four studies have highlighted the use of FANA ASOs in vivo to target Crohn’s disease, androgen receptor (AR)-RNA complexes implicated in cancer, inflammation after spinal cord injury, and angiogenesis . A fifth study showcased antibacterial FANA ASOs to tackle citrus greening disease, which affects citrus tree groves worldwide .…”
Section: Discussionmentioning
confidence: 99%
“…FANA ASOs, in particular, have been receiving increased attention. In the past year, four studies have highlighted the use of FANA ASOs in vivo to target Crohn’s disease, androgen receptor (AR)-RNA complexes implicated in cancer, inflammation after spinal cord injury, and angiogenesis . A fifth study showcased antibacterial FANA ASOs to tackle citrus greening disease, which affects citrus tree groves worldwide .…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid analogs have been employed as therapeutic agents in a vast majority of disorders, allowing for sequence specific targeting of genomic or proteomic targets. (42,43,56,57) Of particular interest in this study, we focused on 2'-fluoro-D-arabinonucleic acid analogs (FANAs), as these oligomers have been shown to be self-delivering in vivo and provide effective binding to their targets within both in vitro and in vivo systems. (42)(43)(44) Thus, FANA analogs designed to bind to the miR binding sites could be potentially used as a therapeutic option as a binding inhibitor to block miR binding on the SARS-CoV-2 genome 3'-UTR, relieving the wild-type miRs to perform their normal functions in the host.…”
Section: Utrmentioning
confidence: 99%
“…Antisense oligonucleotides, like 2'-fluoro-D-arabinonucleic acids (FANAs), have been employed in several applications as binding inhibitors or in siRNA knockdowns, and have been theorized and developed to be effective oligos due to their ability to self-deliver in vivo and prove effective in many in vitro systems. (42)(43)(44) Often, antisense oligonucleotides have been employed for these purposes, designed as sequence specific targets, such as for siRNA-mediated knockouts or targeted binding. (42)(43)(44)(45) Thus, FANAs could sequencespecific target these binding interactions and allow for a potential mechanism of intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FANA ASOs have also proven to be more stable than dsRNAs (Ferrari et al, 2006;Hunter et al, 2021) and have shown activity in both the cytoplasm and the nucleus (Liang X.-H. et al, 2017). Perhaps the most intriguing (and most useful) property of FANA ASOs is their capacity for self-delivery (gymnosis), independent of transfection agents (Soifer et al, 2011;Souleimanian et al, 2012;Pelisch et al, 2021). These properties have spurred great interest in utilizing FANA ASOs in a wide array of fields and are of particular interest in biopesticide applications (Hunter et al, 2021;Sandoval-Mojica et al, 2021), especially given the ability of FANA ASOs to target bacteria.…”
Section: Direct Deliverymentioning
confidence: 99%